Novel Incentive Mechanism for End-Users Enrolled in DLC-Based Demand Response Programs Within Stochastic Planning Context - Erdinc, Ozan; Tascikaraoglu, Akin; Paterakis, Nikolaos G.; Catalao, Joao P. S. (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2019)
In this paper, a novel direct load control (DLC) planning based on providing free energy credits to residential end-users for their heating, ventilation, and air conditioning load during demand response (DR) events is proposed. The obtained credit can then be used by the end-users during relatively higher price periods free-of-cost to enable them lowering their energy procurement costs. Furthermore, the resulting reduction in the total household energy consumption considerably decreases the critical load demands in power systems, which is of vital importance for load-serving entities in maintaining the balance between supply and demand during peak load periods. In this regard, the aforementioned energy credits-based incentive mechanism is proposed for end-users enrolled in the DLC-based DR program, as a new contribution to the existing literature, testing it in a stochastic day-ahead planning context.
Keywords: Demand response (DR); direct load control (DLC); energy credit; heating; ventilation; and air; THERMOSTATICALLY CONTROLLED LOADS; ENERGY MANAGEMENT-SYSTEM; CONTROLLED APPLIANCES; HVAC SYSTEMS; SMART GRIDS; IMPACT; OPTIMIZATION; GENERATION; DEVICES; SERVICE; Automation & Control Systems; Engineering; Instruments & Instrumentation